Determinant factors of part-time employment among undergraduate students / Amir Imran Ramli, Muhammad Afif Akmal Md Alkhan and Muhammad Muzaimy Rahemi - Ramli, Amir Imran; Md Alkhan, Muhammad Afif Akmal; Rahemi, Muhammad Muzaimy (2021)
Part-time job is a form of employment where a worker performs a certain number of hours less than a full-time worker. Part-time job is one of the most popular ways for university students to earn extra income. There are several reasons in which drive the students to do part-time job as a big commitment to survive with their own pocket money and family’s budgeting ﬁnance and their study ﬂexibility as they are not able to go to university. Thus, this study’s aim is to focus on determinant factors in venturing part time work among university students in Malaysia. A total of 212 students participated in this study. Respondents were given an online survey with a certain set of questions regarding part-time jobs. Logistic regression analysis was used to determine the purposes of doing part time job while studying. Hosmer and Lemeshow test (p=0.013) reveals that the model was a good ﬁt for the data when compared to the 0.05 signiﬁcant level. Cox Snell R2 and Nagelkerke R2 provide 27.4% and 36.6% total variation respectively which related to all independent variables included. The model efﬁciently predicts the overall outcome which was students that work part-time with 71.5% accuracy. Wald statistics shows that the perception, ﬁnancial constraint and working experience, (p=0.000) were signiﬁcant. It showed that all the variables are affecting the inﬂuence of students to work part-time.